The design and application of in-depth interviews in primary care research - Zhijie Xu; Yang Wang; Yi Qian (Chinese General Practice Journal, 2025)
In-depth interviews aim to explore the lived experiences and behavioral patterns of specific social groups through detailed conversations with participants. This qualitative method is used to investigate the underlying processes behind particular phenomena and to generate insights and recommendations for problem-solving. In recent years, in-depth interviews have been widely applied in primary care research. Therefore, a solid understanding of the fundamental concepts, as well as the design and implementation of this method, is essential for researchers in the field. This paper systematically outlines the research process of conducting in-depth interviews across three key stages: before, during, and after the interviews. Prior to initiating an in-depth interview study, researchers need to familiarize themselves with the method's theoretical foundations, distinctive features, and limitations, in alignment with their research goals and processes, to determine its suitability. During the design and implementation phase, attention should be paid to four core steps: recruiting participants, developing and refining the interview guide, collecting interview data, and conducting data analysis. After the analysis is completed, researchers should write and report their findings in accordance with qualitative research reporting standards to enhance the credibility and transparency of their study. Additionally, this paper highlights five areas within primary care where in-depth interviews are particularly applicable, and it introduces useful learning resources to support researchers in mastering this method. By presenting a comprehensive overview of in-depth interviews, this paper aims to equip primary care researchers with a practical and rigorous qualitative method, contributing to improved methodological quality in primary care research.